Teori Kognitivsme dan Implementasinya dalam Kurikulum Merdeka Belajar - Ara, Tyara Maharani; Andika Apriansyah; Juli Setio; Kasinyo Harto; Amilda (Bedelau: Journal of Education and Learning, 2024)
This article aims to discuss cognitive theory and its implementation in the independent learning curriculum. This research uses a literature study research method. Relevant library sources are primary data sources (research results data, research reports, scientific journals, etc. Secondary data sources (basic government legal regulations, books, etc.) are the data sources used in this research. Cognitivist learning theory is very relevant to This freedom of learning is because freedom of learning prioritizes the process rather than the results. This can be proven through the implementation of freedom of learning which requires forming the character of students in teaching and learning activities. Likewise, this can be implemented through increasing good interactions between educators and students by conducting discussions on learning activities. Other things are also done, such as eliminating KKM, which is in line with the opinion of cognitivist learning theory which prioritizes processes rather than outcomes with other stages. So teachers should really understand the stages of cognitive development of each student.